Understanding smartphone usage in college classrooms: A long-term measurement study. (November 2019) - Kim, Inyeop; Kim, Rihun; Kim, Heepyung; Kim, Duyeon; Han, Kyungsik; Lee, Paul H.; Mark, Gloria; Lee, Uichin
Abstract: Smartphone usage is widespread in college classrooms, but there is a lack of measurement studies. We conducted a 14-week measurement study in the wild with 84 first-year college students in Korea. We developed a data collection and processing tool for usage logging, mobility tracking, class evaluation, and class attendance detection. Using this dataset, we quantify students' smartphone usage patterns in the classrooms, ranging from simple use duration and frequency to temporal rhythms and interaction patterns. Furthermore, we identify the key predictors of students' in-class smartphone use and their semester grades. Our results reveal that students use their phones for more than 25% of effective class duration, and phone distractions occur every 3–4 min for over a minute in duration. The key predictors of in-class smartphone use are daily usage habits and class characteristics, and in-class phone usage is negatively correlated with student grades. Highlights: Students used their phones for more than 20 min per class, which is over 25% of the effective class duration. Phone usage was prevalent throughout the class, and phone distractions happened in every 3–4 min for over a minute. Considerable underestimation of in-class phone usage was found: self-report: 8.25 vs. measurement: 12.28 Predictors of in-class usage were daily usage behaviors, class size, and lecture organization. Phone usage patterns such as daily and in-class use habits had a negative relationship with student grades.